DINAMIKA INTERAKSI AGEN DAN STRUKTUR DALAM MENCEGAH KONSENTRASI KEPEMILIKAN MEDIA TELEVISI - Nusatyo Nursatyo (Universitas Muhammadiyah Surakarta, 2016)
The acquisition PT IDKM by PT EMTEK that have an impact of the unification INDOSIAR and SCTV in the same holding company between period 2011 – 2012, bring a nation-wide discussion about concentration of media television ownership in Indonesia. Broadcast act no.32/2002 with Indonesia Broadcasting Commision as an independent regulatory body considered weak in the face of concentration. This paper provide a comprehensive description about the dynamics interaction between agent and structure of Indonesian broadcasting system particularly in order to organize commercial television media ownership.